Peran Fasilitator Puspaga dalam Pelaksanaan Sosialisasi Parenting dan Sekolah Orang Tua Hebat (SOTH) di DP3APPKB Kota Surabaya - Alifatul Reniwati Zumroh; Sri Kamariyah; Nihayatus Sholichah; Kristyan Dwijosusilo; Widyawati Widyawati; Zainal Fatah; Dandi Patrija Wirawan (Abdimas Indonesian Journal, 2026)
Child parenting is a crucial aspect in supporting optimal child development; however, it continues to face various challenges, including limited parental knowledge, low family communication skills, and the persistence of violence against children. The Surabaya City Government, in collaboration with the National Population and Family Planning Board (BKKBN), initiated the Sekolah Orang Tua Hebat (SOTH) Program as a family-based educational intervention implemented through the Pusat Pembelajaran Keluarga (PUSPAGA) services. This community service article aims to describe the role of PUSPAGA facilitators in the implementation of parenting socialization and the SOTH Program at DP3APPKB Surabaya City, particularly through the involvement of students from the Certified Internship and Independent Study Program (MSIB) Batch 5 at the neighborhood (Balai RW) level in Margorejo Sub-district. A participatory approach was employed by directly involving students in socialization activities and educational assistance within the community. The results indicate an improvement in parents’ understanding and awareness of positive parenting practices, effective family communication, and the prevention of child and adolescent issues. Furthermore, the involvement of MSIB students strengthened the role of PUSPAGA facilitators as a bridge between government policies and community needs at the local level.